2021
DOI: 10.3390/microorganisms9051072
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric-Pressure Plasma Caused Protein Damage in Methicillin-Resistant Staphylococcus aureus Cells in Biofilms

Abstract: Biofilms formed by multidrug-resistant bacteria are a major cause of hospital-acquired infections. Cold atmospheric-pressure plasma (CAP) is attractive for sterilization, especially to disrupt biofilms formed by multidrug-resistant bacteria. However, the underlying molecular mechanism is not clear. In this study, CAP effectively reduced the living cells in the biofilms formed by methicillin-resistant Staphylococcus aureus, and 6 min treatment with CAP reduced the S. aureus cells in biofilms by 3.5 log10. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
(68 reference statements)
1
17
0
Order By: Relevance
“…Because of the non-selectivity of reactive oxygen species and reactive nitrogen species, they highly react with biological macromolecules—DNA and proteins—and cause damage. The ROS of LTGP inevitably induced DNA damage, such as double-strand break and DNA-protein crosslinking [ 9 , 35 , 36 ]. Quinolone antibiotics, ciprofloxacin and norfloxacin, impede DNA replication, which is also blocked by DNA damage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the non-selectivity of reactive oxygen species and reactive nitrogen species, they highly react with biological macromolecules—DNA and proteins—and cause damage. The ROS of LTGP inevitably induced DNA damage, such as double-strand break and DNA-protein crosslinking [ 9 , 35 , 36 ]. Quinolone antibiotics, ciprofloxacin and norfloxacin, impede DNA replication, which is also blocked by DNA damage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biofilms were cultured as described previously [ 9 , 29 ]. S. aureus ATCC33591, a methicillin-resistant strain, was purchased from the American Type Culture Collection (ATCC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These molecules play a significant role in the plasma biocidal process by altering the cell-wall components, the functions and structure of the phospholipid bilayer, the structure of nucleic acids and cellular proteins, gene expressions, and protein synthesis [26,29,30]. It was shown that cold plasma reduced the colony-forming unit (CFU) in Staphylococcus aureus biofilms within 6 min [31]. Inoculated Gram-positive Bacillus subtilis on black peppercorn surfaces were reduced by five orders of magnitude within 300 s, while the Gram-negative Salmonella enteritidis were totally eradicated by seven orders of magnitude [32].…”
Section: Introductionmentioning
confidence: 99%